Employee Brand Engagement on Social Media: Managing Optimism and Commonality - Pitt, C. (2019)
This article considers how employees engage with B2B firms on social media, a topic that is largely overlooked in the extant brand engagement literature. Using the results from a large-scale study of employee brand engagement on social media, we identify two key drivers of employee brand engagement using the content analysis tool DICTION–—namely, optimism and commonality. Employees of top-ranked and -rated firms express higher levels of optimism and commonality in their reviews of their employers on social media than do their counterparts in bottom-ranked and-rated firms. This permits the construction of a 2 X 2 matrix that allows managers to diagnose strategies for increasing or improving employee brand engagement. This creates four different kinds of employee brand engagement situations, and offers human resources and marketing managers different strategies in each case. We demonstrate how practitioners and scholars can shed new light on the way stakeholders engage with brands